2005
DOI: 10.1084/jem.20041617
|View full text |Cite
|
Sign up to set email alerts
|

NK cell activation through the NKG2D ligand MULT-1 is selectively prevented by the glycoprotein encoded by mouse cytomegalovirus gene m145

Abstract: The NK cell–activating receptor NKG2D interacts with three different cellular ligands, all of which are regulated by mouse cytomegalovirus (MCMV). We set out to define the viral gene product regulating murine UL16-binding protein-like transcript (MULT)-1, a newly described NKG2D ligand. We show that MCMV infection strongly induces MULT-1 gene expression, but surface expression of this glycoprotein is nevertheless completely abolished by the virus. Screening a panel of MCMV deletion mutants defined the gene m14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
117
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 48 publications
5
117
0
Order By: Relevance
“…Until now, no report including our preliminary study (data not shown) demonstrates that HBsAg has the character. Also, virus proteins such as MCMV m155-, m145-, m152-or m138-encoded glycoprotein may induce the virus infected cells to down-express or upexpress the ligands of activating NK cell receptor (so called ''induced-self'' or ''missing-self'', respectively), by which NK cells may attack self-tissue too [34][35][36][37][38]. We practiced the experiments to explore the ligands of activating NK cell receptor on hepatocytes of HBsAg transgenic mice, and no significant change was found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, no report including our preliminary study (data not shown) demonstrates that HBsAg has the character. Also, virus proteins such as MCMV m155-, m145-, m152-or m138-encoded glycoprotein may induce the virus infected cells to down-express or upexpress the ligands of activating NK cell receptor (so called ''induced-self'' or ''missing-self'', respectively), by which NK cells may attack self-tissue too [34][35][36][37][38]. We practiced the experiments to explore the ligands of activating NK cell receptor on hepatocytes of HBsAg transgenic mice, and no significant change was found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, 11 other ORFs in MCMV were also shown to have MHC-like folds and to be transmembrane glycoproteins (26). Three of these, m145, m152, and m155 have subsequently been shown to sequester stress-induced molecules (MULT1, RAE1, and H60, respectively) that would normally engage the NKG2D-activating NK receptors and interfere with NK cell activation and virus control (27)(28)(29)(30). UL16 of HCMV is known to sequester only some of the human ligands for NKG2D: it does not affect MICA or ULBP3.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations have shown that three other ORFs which had been identified as having MHC-like folds in MCMV, m145 and m155, were able to mediate NK evasion, as these molecules sequestered cellular ligands that would bind the activating NK receptor NKG2D (27)(28)(29)(30).…”
Section: Low Passage and Clinical Isolates Of Hcmv Encode An Additionmentioning
confidence: 99%
“…Remarkably, these NKG2D ligands are related to MHC class I (MHC-I)-like molecules (11,12), and several are targets of MHC-I-like immunoevasins (3). In particular, mouse CMV (MCMV) m152/gp40 (hereafter referred to as "m152") has a dual role, downregulating cell-surface expression of RAE1 family members [but not MULT1 or H60 (13), the targets of MCMV proteins m145 and m155, respectively (14,15)] as well as host MHC-I molecules (16)(17)(18)(19). A virus-encoded Fc receptor, m138, also controls MULT1, H60 (3), and RAE1ε (20).…”
mentioning
confidence: 99%